KAJIAN PENGARUH SUHU TERHADAP VISKOSITAS MINYAK GORENG SEBAGAI RANCANGAN BAHAN AJAR PETUNJUK PRAKTIKUM FISIKA - Yanisa Damayanti; Albertus Djoko Lesmono; Trapsilo Prihandono (JURNAL PEMBELAJARAN FISIKA, 2018)
Viscosity was the friction that occurs between layers in the fluid. There were several factors that affect the viscosity value of a fluid, one of them was temperature. But the effect of temperature on viscosity was still rarely discussed in the learning. This research aim to examine the effect of temperature on the cooking oil viscosity and made the design of physics practical work guideline based on the results of research. The fluid used in this research was oil palm packing oil consisting of Bimoli, Filma and Kunci Mas. In this research, the effect of temperature on the cooking oil viscosity was using the Stokes law. The result of the research was used as the basis for teaching material physics practical work guideline. Based on the results of the research showed that the viscosity of cooking oil decreased with increasing temperature. This was indicated by the declining mass of cooking oil. The design of physics practical work guideline of temperature effect on viscosity consists of several parts, the title, purpose, tools and materials, theoretical basis on the effect of temperature on viscosity, step experiment, experiment result tabel, and question.Key word: viscosity, temperature, cooking oil, teaching material.